2007
DOI: 10.1088/1126-6708/2007/10/025
|View full text |Cite
|
Sign up to set email alerts
|

Orientifold's landscape: non-factorisable six-tori

Abstract: We construct type IIA orientifolds on T 6 /Z 2 × Z 2 which admit non factorisable lattices. We describe a method to deal with this kind of configurations and discuss how the compactification lattice affects the tadpole cancellation conditions. Moreover, we include D6-branes which are not parallel to O6-planes. These branes can give rise to chiral spectra in four dimensions, thus uncovering a new corner in the landscape of intersecting D-brane model constructions. We demonstrate the construction at an explicit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 89 publications
(130 reference statements)
1
20
0
Order By: Relevance
“…2 Another, empirical, observation favouring the discrete torsion orbifolds has been made in [57]: In cases where there are no three family models without discrete torsion (viz. Z 2 × Z 2 on the AAA lattice [53,54] or on non-factorisable T 6 -orbifolds [58]) it has been demonstrated that with discrete torsion and rigid D6-branes there are three family models.…”
Section: Introductionmentioning
confidence: 99%
“…2 Another, empirical, observation favouring the discrete torsion orbifolds has been made in [57]: In cases where there are no three family models without discrete torsion (viz. Z 2 × Z 2 on the AAA lattice [53,54] or on non-factorisable T 6 -orbifolds [58]) it has been demonstrated that with discrete torsion and rigid D6-branes there are three family models.…”
Section: Introductionmentioning
confidence: 99%
“…Section 3 discusses how to represent cycles wrapped by D6-branes. Here we follow and supplement the presentation of [48,50]. A D6-brane is, as in the factorisable case, described by three pairs of wrapping numbers.…”
Section: Jhep03(2015)110mentioning
confidence: 99%
“…The product is to be understood as the cross product 1 mapping a triplet of one-cycles in T 2 to a three-cycle in T 2 × T 2 × T 2 . However, with some modifications this notion can also be carried over to the non-factorisable T 6 = R 6 /Λ SO (12) [48]. 2 Most easily this can be seen if (we drop the brane label a in the present discussion)…”
Section: Jhep03(2015)110mentioning
confidence: 99%
See 1 more Smart Citation
“…We restrict attention to factorizable tori, T 6 = T 2 × T 2 × T 2 . For a discussion of the non-factorizable case see the recent papers [43,44].…”
Section: Jhep08(2008)016mentioning
confidence: 99%